Factors Influencing Educational Policy Implementation in Basic Schools in Ilorin West Local Government Area, Kwara State - BASHIR, B. T.; ISSAH, J.; SALMAN, Arisekola Azeez (International Journal of Educational Management, 2021)
This paper examined factors influencing educational policy implementation in basic schools in Ilorin west local government area, kwara state. A correlation survey research design was used. Random sampling technique was used to select 200 teachers(43%) out of 465 in six of the eleven basic schools in Ilorin west local government with the nomenclature of being upgraded from primary to lower and upper basic schools in 2006. Two research questions were raised and answered while two hypotheses were formulated and tested using percentages and Pearson Product moment correlation statistic at .05 level of significant respectively. The findings revealed that there was significant relationship between factors and educational policy implementation in basic schools in Ilorin west local government area, kwara State. It was recommended among others that; Political elite should be committed in will power to provide the needed facilities for UBE as stated in the white paper, relevant sectors and ministries such as National Directorate of Employment (NDE), Central Bank of Nigeria (CBN), River Basins, Agricultural Institutes, Research Institutes and donor agencies should link up with UBE schools in the supply of equipments, training and employment of teachers and recipients of the programme, School administrators should invite individuals, industries, firms, market women, trade association, artisans and professional groups within the locality as part of management to constitute diverse committees of ensuring UBE success, the constituted management in various committees should ensure compliance for image promotion in providing schools with relevant aid as technical advice, financial, skills germane to reduce inequalities, dependencies and so on the intending beneficiaries of UBE.